PRESENCE OF HEPATITIS C VIRUS INFECTION AMONG DIABATIC PATIENTS IN FAISALABAD, PAKISTAN - K.M. Yahya; K. Iqbal (Journal of University Medical & Dental College, 2012)
ABSTRACT Introduction: Patients with chronic hepatitis C virus (HCV) infection have a significantly increased prevalence of Type 2 Diabetes Mellitus (DM) compared to controls or HBV patients, independent of the presence of cirrhosis. Moreover, antecedent HCV infection markedly increases the risk of developing DM in susceptible subjects. Even non-diabetic patients have insulin resistance and specific defects in the insulin signaling pathways. Subjects and Methods: It was cross-sectional study carried out in different hospitals of Faisalabad. Blood from 154 patients with Diabetes Mellitus attending Out Patients clinic was tested for anti HCV antibodies using a commercial second generation enzyme linked immunosorbent assay (ELISA). Results: Out of 154 diabetic patients, 18.83% (n=29) were positive for anti HCV antibody. The highest prevalence of anti HCV antibody was seen in the age group 41-50 years (29.26)%. The prevalence of HCV was 22.47% among female diabetic patients as compared to 13.84% in male patients. Conclusion: The prevalence of HCV infection among diabetic population of Faisalabad is very high, 2-3 times of normal healthy population as reported by Pakistan Medical Research Council (PMRC).